Exploring sugar allocation and metabolic shifts in cassava plants infected with Cassava common mosaic virus (CsCMV) under long-day photoperiod: diel changes in source and sink leaves - Zanini, Andrea Alejandra (2025)
Cassava common mosaic virus (CsCMV) is a potexvirus that impairs chloroplast and metabolism, causing significant yield losses to cassava crops. Crop yield depends on diel rhythms, influencing carbon allocation and growth, and sugar signaling also impacting light–dark rhythms. This study aimed to elucidate the early impact of CsCMV infection on diel carbon allocation, metabolism, and defense mechanisms in both source and sink cassava leaves before storage root bulking. Soluble sugar and starch concentrations were examined over a 24-h cycle (16:8 photoperiod) in CsCMV-infected plants. The expression of an array of genes—carbohydrate metabolism, SnRK1 activity marker, defense, circadian marker—was analyzed at ZT6, ZT16 and ZT24/ZT0. In CsCMV-infected source leaves, at ZT6, sucrose increased whereas glucose, fructose and sucrose rose at night. An increase in Suc:hexose ratio and upregulation of SnRK1 activity marker genes and PR1 transcripts were found in infected leaves, suggesting a combination of altered carbon metabolism and defense response mechanisms against the viral infection. GIGANTEA, a clock-controlled gene, showed a reduced expression in infected leaves at ZT6 and ZT24/ ZT0, suggesting a circadian phase shift compared with uninfected control plants. Additionally, starch mobilization transcripts were downregulated at ZT24/ZT0, though starch content remained unchanged during the 24-h cycle. In sink leaves, a transient peak of maltose (ZT6) was observed. Our findings suggest that CsCMV disrupts the plant's natural rhythms of sugar metabolism and allocation. Spikes in sucrose levels may serve as infection signals in the internal daily clock of the plant, influencing plant responses during the cassava-CsCMV interaction.